ASSEMBLED DEVICE FOR PLANT CULTIVATION - LEE, HYEON HWA; MUN, KI PYO; SONG, GYUNG UI; LEE, YOUNG SUK (2016)
According to an embodiment of the present invention, an assembled device for plant cultivation comprises: growth cabinets having a space in which plants can be stacked therein and a plurality of holding grooves in the height direction along the width direction of both sides; and a pendant in which a shape corresponding to the holding groove of the growth cabinet is formed in mirror planar symmetry around an imaginary surface that an upper part and a lower part cross from the upper surface center to the lower surface center, and a connection hole connected with a spray unit of spraying liquid is formed at equal intervals along the height direction in the center, wherein a plurality of growth cabinets are assembled in multiple stages along the height direction through the medium of the pendant. 본 발명의 일실시예에 따른 조립식 재배기는 내부에 식물이 적재될 수 있는 공간이 마련되며 양측면 폭방향을 따라 다수개의 거치홈이 높이방향으로 형성되는 재배상; 및 상부 및 하부가 상면 중앙에서 하면 중앙을 가로지르는 가상의 면을 기준으로 상기 재배상의 거치홈에 대응되는 형상이 거울면 대칭으로 형성되고, 중앙부에는 높이방향을 따라 등간격으로 액체를 분사하는 분사부가 연결 설치될 수 있는 연결공이 형성된 지주대;를 포함하되, 다수개의 상기 재배상이 다수개의 상기 지주대를 매개로 높이방향을 따라 다단으로 조립되는 것을 특징으로 하는 조립식 재배기.